Metabolic reprogramming and transcriptomic adaptation contribute to glyphosate resistance in potato cultivars - Xiao, Chunfang; Gao, Jianhua; Zeng, Yuting; Zou, Ying; Wang, Zhen; Zhang, Denghong; Yan, Lei; Yang, Guocai; Shen, Yanfen (Frontiers in Plant Science, 2026)
Glyphosate, a widely used herbicide, inhibits 5-enolpyruvylshikimate-3-phosphate synthase in the shikimate pathway, and its repeated application has led to resistance in several crops, including potato. In this study, we investigated the molecular and metabolic mechanisms underlying glyphosate resistance in two contrasting potato cultivars, DP (glyphosate-tolerant) and MA (glyphosate-sensitive), using integrated transcriptomic and metabolomic analyses. Glyphosate treatment triggered cultivar-specific responses: although both cultivars activated early stress-related pathways, DP exhibited a more coordinated and sustained transcriptional response, particularly in pathways associated with detoxification, redox homeostasis, and energy regulation, whereas MA showed a broader but less organized response mainly enriched in photosynthesis and carbohydrate metabolism. Metabolomic analysis revealed pronounced metabolic reprogramming in DP, including enhanced flux through the shikimate and phenylpropanoid pathways and increased accumulation of tyrosine, ferulic acid, and flavonoids, which contribute to oxidative stress mitigation and structural defense. In contrast, MA displayed weaker metabolic adjustments, especially in secondary metabolism. Overall, these results demonstrate that glyphosate resistance in potato is driven by transcriptional plasticity and metabolic reprogramming that enhance secondary metabolism and stress tolerance, providing new insights into herbicide resistance mechanisms.